Health and Quality of Life Outcomes - Oremus, Mark.; Schunemann, Holger J.; Xie, Feng.; Rivero-Arias, Oliver; Rencz, Fanni; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Health and Quality of Life Outcomes is an open access, peer-reviewed journal offering rapid publication and wide diffusion in the public domain of high-quality articles in the field of Health-Related Quality of Life (HRQOL). Health and Quality of Life Outcomes considers original research manuscripts using appropriate quantitative or qualitative methods, systematic reviews/meta-analyses, seminar papers, study protocols, commentaries on articles, and letters to the editor where the main focus is HRQOL. We welcome contributions in the following areas: Hypothesis-based or theory-driven primary or secondary analyses using observational or experimental data using HRQOL information as an independent or dependent variable; Systematic reviews and/or meta-analyses of HRQOL studies following appropriate reporting guidelines (e.g., PRISMA); Articles describing novel theoretical frameworks created to underpin the development or use of HRQOL instruments; Submissions describing the psychometric properties of instruments measuring HRQOL or similar patient reported outcomes, including the validation of existing instruments in new populations, settings, or contexts; Methodological and applied research using preference elicitation exercises to report the estimation of value sets to inform health valuation; and Study protocols of planned or ongoing research studies, provided data collection is not complete and analyses have not yet begun. To encourage the submission of high-quality work, all manuscripts submitted to the journal should conform to the relevant reporting guidelines (e.g., PRISMA, PRISMA-P, MOOSE, STROBE, CONSORT). Systematic reviews/meta-analyses and randomized controlled trials will only be considered for publication if they are preceded by a registry listing (e.g., PROSPERO, clinicaltrials.gov) or a published study protocol.
Keywords: Quality of life; Psychology$1 (BMethodology.s; Psychological tests; Sampling (Statistics).; Quality of Life Research; Psychological Methods; Psychological Assessment; Methodology of Data Collection and Processing